The Influence of Leadership, Work Environment, and Discipline on Work Performance: Pengaruh Kepemimpinan, Lingkungan Kerja, dan Disiplin Terhadap Kinerja Kerja - Agustini, Elly; Sari, Herlinda Maya Kumala (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of leadership, work environment and discipline on employee performance (Case Study: Bmt Madani in Taman, Sidoarjo – East Java). The method used in this research is a quantitative approach. Sampling in this study was carried out by saturated sampling method, with the number of respondents as many as 55 respondents from BMT Madani employees. The data analysis technique used in this study used the SPSS version 24 program. The results of this study prove that Leadership has a positive and significant effect on the performance of BMT Madani employees, the Work Environment has a positive and significant effect on the performance of BMT Madani employees, Discipline has a positive and significant effect on the performance of BMT Madani employees. Leadership Work Environment and Discipline have a simultaneous effect on Employee Performance at BMT Madani (Case Study: BMT Madani in Taman, Sidoarjo – East Java).